Rejuvenating the mature business : the competitive challenge - Baden-Fuller, C. 1948- (Routledge, 1992)
This book presents: Maturity, a state of mind; The firm matters, not the industry; Strategic innovation; Choosing the strategic territory; The entrepreneurial organisation; The crescendo model of rejuvenation...